2017
DOI: 10.1111/evo.13229
|View full text |Cite
|
Sign up to set email alerts
|

Genomic changes following the reversal of a Y chromosome to an autosome inDrosophila pseudoobscura

Abstract: Robertsonian translocations resulting in fusions between sex chromosomes and autosomes shape karyotype evolution by creating new sex chromosomes from autosomes. These translocations can also reverse sex chromosomes back into autosomes, which is especially intriguing given the dramatic differences between autosomes and sex chromosomes. To study the genomic events following a Y chromosome reversal, we investigated an autosome-Y translocation in Drosophila pseudoobscura. The ancestral Y chromosome fused to a smal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 103 publications
(175 reference statements)
1
21
0
Order By: Relevance
“…The Y--derived material on the dot of D. miranda amounts to approximately 300 kb, which is substantially smaller than Y chromosomes found in Drosophila [53], suggesting that Y anc presumably lost genetic material after fusing to the dot chromosome. Similar shrinkage of the Y anc was found in its sister species D. pseudoobscura [18], which shows an inversion of the Y--derived segment with respect to D. miranda ( Figure S17). The Y anc / element F fusion breakpoint is corroborated independently by a BAC clone spanning the fusion (Figure S17), validating our genome assembly in this region.…”
Section: Reconstruction Of Chromosomal Events Leading To Sex Chromososupporting
confidence: 70%
“…The Y--derived material on the dot of D. miranda amounts to approximately 300 kb, which is substantially smaller than Y chromosomes found in Drosophila [53], suggesting that Y anc presumably lost genetic material after fusing to the dot chromosome. Similar shrinkage of the Y anc was found in its sister species D. pseudoobscura [18], which shows an inversion of the Y--derived segment with respect to D. miranda ( Figure S17). The Y anc / element F fusion breakpoint is corroborated independently by a BAC clone spanning the fusion (Figure S17), validating our genome assembly in this region.…”
Section: Reconstruction Of Chromosomal Events Leading To Sex Chromososupporting
confidence: 70%
“…azteca , and D . affinis ) all formerly Y-linked genes ( kl-2 , kl-3 , PPr-Y , ORY , and ARY ) acquired autosomal linkage [ 21 ]; mapping and sequencing experiments showed that they moved to the small "dot chromosome" [ 22 ], amazingly remaining side-by-side [ 21 , 23 ]. However, given the findings on the montium species, one may also think that the pseudoobscura lineage is similar to what we would had observed in montium if we had sampled only the auraria clade ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…melanogaster [ 58 , 59 ], although we should keep in mind that nothing is known about the rate of rearrangements in the Drosophila Y. Such test must be done by fluorescent in situ hybridization (FISH), or by a long-read assembly [ 23 ], since Sanger or Illumina assemblies are too fragmented to provide synteny information of repetitive regions. Second, since two gene copies (Y and autosomal/X-linked) seem to have co-existed for a long time, one might expect to see both in some species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When linkage disequilibrium, mutation rates, and recombination rates are compared between the F–E fusion chromosome in D. willistoni and the other chromosomes, no significant differences are found, in contrast to what is typically seen for the D. melanogaster F element ( Powell et al 2011 ). Equilibration of recombination rates between two recently joined distinct domains is underway in D. busckii , where the dot chromosome is fused to the X and Y chromosomes, creating a neo-X and a neo-Y chromosome ( Zhou and Bachtrog 2015 ); the opposite example, an old Y chromosome fusing to the dot chromosome, has also been observed ( Chang and Larracuente 2017 ). In D. busckii , the F element portion of the neo-Y chromosome is undergoing rapid changes leading to degeneration, with many more single-nucleotide polymorphisms, and insertions and deletions being detected in the neo-Y than the neo-X ( Zhou and Bachtrog 2015 ).…”
Section: The Evolutionary History Of the F Element Within The Genus mentioning
confidence: 99%